2022
DOI: 10.5489/cuaj.7860
|View full text |Cite
|
Sign up to set email alerts
|

UPDATE – 2022 Canadian Urological Association best practice report: Vasectomy

Abstract: The following is an update of the 2016 Canadian Urological Association vasectomy guideline. The changes introduced are relatively minor, and include:-Clarified text on the optimal vasectomy occlusion technique, with a statement added about the surgeon being able to choose his/her preferred technique so long as outcomes are good. -Clarification of the recommendations on the number of post-vasectomy semen analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…This study also highlighted the association of hematomas with scrotal infection with or without abscess. This finding supports the use of minimally invasive technique such as NSV to reduce both the risks of bleeding and infection as recommended in recent vasectomy guidelines ( 3 , 19 , 20 , 22 ). We fortuitously identified a heart valve infection occurring in a patient who had a recent vasectomy.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This study also highlighted the association of hematomas with scrotal infection with or without abscess. This finding supports the use of minimally invasive technique such as NSV to reduce both the risks of bleeding and infection as recommended in recent vasectomy guidelines ( 3 , 19 , 20 , 22 ). We fortuitously identified a heart valve infection occurring in a patient who had a recent vasectomy.…”
Section: Discussionsupporting
confidence: 83%
“…They stopped using ligation and excision with FI on the testicular end after confirming in their practice the high risk of occlusion failure demonstrated in the Sokal et al randomized trial ( 11 , 12 ). They adopted the thermal cautery of the vas mucosa combined with FI on the prostatic end ( 13 ), recommended in clinical practice guidelines ( 3 , 13 , 19 , 20 ). Colombian surgeons suggested that the use of three silk sutures with the former occlusion technique compared with only one silk suture with the currently used technique may contribute to this difference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation